2010
DOI: 10.1111/j.1751-7915.2010.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the RND family of multidrug efflux pumps: in silico to in vivo confirmation of four functionally distinct subgroups

Abstract: SummaryWe have developed a generalized profile that identifies members of the root‐nodulation‐cell‐division (RND) family of efflux pumps and classifies them into four functional subfamilies. According to Z‐score values, efflux pumps can be grouped by their metabolic function, thus making it possible to distinguish pumps involved in antibiotic resistance (group 1) from those involved in metal resistance (group 3). In silico data regarding efflux pumps in group 1 were validated after identification of RND efflux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 71 publications
(101 reference statements)
1
35
0
Order By: Relevance
“…In this study, we have isolated a mutant in the ttgB gene that exhibited increased sensitivity to chloramphenicol, confirming Godoy and colleagues' observations (23). The TtgABC efflux pump is a multidrug efflux system that expels chloramphenicol from the cell, as it is known to do for tetracycline, ethidium bromide, ampicillin, and other antibiotics (14,18,23,58).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In this study, we have isolated a mutant in the ttgB gene that exhibited increased sensitivity to chloramphenicol, confirming Godoy and colleagues' observations (23). The TtgABC efflux pump is a multidrug efflux system that expels chloramphenicol from the cell, as it is known to do for tetracycline, ethidium bromide, ampicillin, and other antibiotics (14,18,23,58).…”
Section: Discussionsupporting
confidence: 66%
“…Genome annotation of several natural chloramphenicol-resistant P. putida strains failed to show any specific chloramphenicol-modifying enzymes (36,41,45,67); however, Godoy and colleagues (23) showed that P. putida mutants in the multidrug TtgABC pump exhibited compromised growth in the presence of chloramphenicol (21). Further studies in P. putida DOT-T1E confirmed the role of the TtgABC efflux pump in tolerance to chloramphenicol and other toxic compounds while unveiling the molecular mechanisms involved in the regulation of the expression of this pump in this strain (14,18,58).…”
mentioning
confidence: 99%
“…Their regulators (e.g., MexR, EsrC, ArmZ, and MexT) can respond to various stresses caused by, for example, membrane-damaging or ribosome-disrupting agents, reactive oxygen species, and/or nitrosative stress and subsequently cause increased activities of these pumps against the stresses (441,454,461,467,798,799,827,835,911). Consistently, P. putida RND pump mutants are categorized into 4 functionally distinct subgroups, and one of them is more susceptible to oxidation-inducing agents (912). In a situation mimicking chronic cystic fibrosis infections with antibiotic therapy, oxidative stress and antibiotic exposure result in the hyperexpression of AmrAB-OprM of Burkholderia vietnamiensis (913).…”
Section: Bacterial Stress Responsesmentioning
confidence: 85%
“…911 RND family efflux pumps play a major role in multidrug resistance in Gram-negative bacteria. AcrB is an obligate trimer that exists and functions exclusively in the trimeric form (Figure 1A).…”
mentioning
confidence: 99%